Court interpreters’ role in upholding the principle of language in legal proceedings: Kazakhstan case - Adilmuratova, Rita; Alembayev, Kairat; Kozhuganova, Dinara; Gavrilova, Yuliya; Menzyuk, Galina (Comparative Legilinguistics, 2024)
The demographic shifts in Kazakhstan impact legal proceedings, with a growing number of participants who lack proficiency in the language of court proceedings. This highlights the importance of employing court interpreters. The purpose of the article was to reveal the importance of this specialist in the process of considering a case and providing citizens with the right to justice. The following methods were used in the study: analysis, synthesis, comparison, legal doctrinal, comparative, abstraction. As a result, a number of problems were revealed regarding the implementation of professional activities by a court translator in the Republic of Kazakhstan. The study conducted a comparative analysis of court interpreters in Kazakhstan and foreign jurisdictions, highlighting commonalities and differences in their legal status, authority, and qualifications. In addition, as a result of the study, statistical indicators were presented describing the number of cases considered by the courts of the Republic of Kazakhstan with the participation of foreign citizens. The study yielded recommendations for establishing a centralized database of court interpreters in Kazakhstan and refining candidate requirements, especially concerning education levels. These insights can inform the development of training programs and certification processes for translators in the country.